REMOTE WORK BETWEEN NARRATIVES OF INDIPENDENCE AND FRACTURED EXPERIENCES. A QUALITATIVE RESEARCH DURING THE PANDEMIC CRISIS. - Risi, Elisabetta; Pronzato, Riccardo (AoIR Selected Papers of Internet Research, 2021)
This paper focuses on how remote workers experienced their job and everyday life during the Italian lockdown imposed by the national government to contain the spread of COVID-19. Specifically, this contribution focuses on the interdependence of work and everyday life, and the role of digital devices and online platforms during the home-confinement period, and it explores the consequences of social distancing measures on remote workers and on their working and personal conditions. The study draws from 20 in-depth semi-structured interviews with remote workers, i.e., individuals which could work from home through digital technologies during the national lockdown. Results highlight that during the lockdown, some participants attempted to cope with the unprecedented triumph of technologically mediated work, others described remote work as liberating and attractive, as it avoids commuting and allow people to organize their activities autonomously, without constraints of space and time. However, their initial enthusiasm decreased after a few weeks of domestic confinement. The experience of remote workers that emerges is a “fractured” one, which appears as a characteristic feature of forced and continuous remote work. Indeed, the coronavirus crisis has accentuated the infrastructural role of digital platforms and intensified the ‘deep mediatization’ of social life and labour, thereby normalizing transmedia work and the ‘extension of already media saturated working conditions’.